Pregunta
upstudy study bank question image url

a) Solve the unknown in each of the following: 8) \( \frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x} \)

Ask by Johnson Joseph. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( x=4 \)

Solución

Solve the equation \( \frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x}\) - step1: Find the domain: \(\frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x},x \in \left(-\infty,2\right)\cup \left(2,3\right)\cup \left(3,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\frac{x}{x-2}\times \left(x-2\right)\left(-x+3\right)=\left(\frac{1}{x-3}-\frac{2}{2-x}\right)\left(x-2\right)\left(-x+3\right)\) - step3: Simplify the equation: \(-x^{2}+3x=8-3x\) - step4: Move the expression to the left side: \(-x^{2}+3x-\left(8-3x\right)=0\) - step5: Calculate: \(-x^{2}+6x-8=0\) - step6: Factor the expression: \(\left(-x+4\right)\left(x-2\right)=0\) - step7: Separate into possible cases: \(\begin{align}&-x+4=0\\&x-2=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=4\\&x=2\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&x=4\\&x=2\end{align},x \in \left(-\infty,2\right)\cup \left(2,3\right)\cup \left(3,+\infty\right)\) - step10: Find the intersection: \(x=4\) The solution to the equation \( \frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x} \) is \( x=4 \).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve the equation \( \frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x} \), first simplify the right side. Notice that \( \frac{2}{2-x} \) can be rewritten as \( -\frac{2}{x-2} \) since they are negatives. Thus, the equation becomes: \[ \frac{x}{x-2} = \frac{1}{x-3} + \frac{2}{x-2} \] Now, combine the fractions on the right-hand side under a common denominator \( (x-3)(x-2) \): \[ \frac{x}{x-2} = \frac{(x-2) + 2(x-3)}{(x-3)(x-2)} \] This simplifies to: \[ \frac{x}{x-2} = \frac{x-2+2x-6}{(x-3)(x-2)} = \frac{3x-8}{(x-3)(x-2)} \] Now, cross-multiply to eliminate the fractions: \[ x(x-3) = (x-2)(3x-8) \] Expanding both sides gives: \[ x^2 - 3x = 3x^2 - 8x - 6x + 16 \] \[ x^2 - 3x = 3x^2 - 14x + 16 \] Rearranging the terms leads to: \[ 0 = 2x^2 - 11x + 16 \] Now, apply the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ x = \frac{11 \pm \sqrt{(-11)^2 - 4 \cdot 2 \cdot 16}}{2 \cdot 2} = \frac{11 \pm \sqrt{121 - 128}}{4} = \frac{11 \pm \sqrt{-7}}{4} \] Since the discriminant is negative, we end up with two complex solutions: \[ x = \frac{11 \pm i\sqrt{7}}{4} \] Thus, the solutions are: \[ x = \frac{11}{4} + \frac{i\sqrt{7}}{4} \quad \text{and} \quad x = \frac{11}{4} - \frac{i\sqrt{7}}{4} \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad